Impact of Pre-Treatment Serum Ferritin on Response and Survival in Myelodysplastic Syndromes Treated With Azacytidine: A Multivariate Analysis - Moreno Carrasco, Gloria; Ortiz-Flores, Rodolfo; García Delgado, Regina; Cidoncha Morcillo, Borja; Rosell-Mas, Ana Isabel; Díaz Canales, Dana; Rodríguez-González, María; Carrasco Gomariz, Manuel; Escamilla-Sánchez, Alejandro (Wiley Gold, 2025)
Background: Myelodysplastic syndromes (MDS) encompass a heterogeneous group of haematological neoplasms characterized by ineffective haematopoiesis and a variable risk of transformation to acute myeloid leukaemia (AML). Elevated serum ferritin (SF), a marker of iron overload (IO), has been linked to poorer outcomes in MDS. However, the impact of pre-treatment SF levels on azacytidine (AZA) response and survival outcomes remains unclear. Methods: This retrospective cohort study included patients with World Health Organization- defined MDS or AML with 20%–30% bone marrow blasts treated with AZA at the Virgen de la Victoria University Hospital (Málaga, Spain) from 2007 onwards. Patients were stratified into three groups based on pre-treatment SF levels: < 500 ng/mL, 500–1000 ng/mL and > 1000 ng/mL. Logistic regression and Kaplan–Meier methods were used to analyse overall response (OR) and overall sur- vival (OS). Results: Among 240 patients, 190 with available SF data were analysed. Patients with SF > 1000 ng/mL showed significantly lower OR (24.2%) and shorter OS (median: 10.1 months) compared to those with SF < 500 ng/mL (OR: 71.4%, OS: 18.2 months) and 500–1000 ng/mL (OR: 82.6%, OS: 20.5 months) (p < 0.0001 for OR, p = 0.001 for OS). Multivariate analysis confirmed elevated SF as an independent predictor of poorer outcomes. Conclusions: Elevated pre-treatment SF levels are strongly associated with reduced response and survival in patients with MDS or AML treated with AZA. Early IO management, such as iron chelation, may improve treatment outcomes.
Keywords: Síndromes mielodisplásicos; Marcadores bioquímicos; Supervivencia; Pronóstico médico; azacytidine; ferritin; hypomethylating agents; iron overload; myelodysplastic syndrome; overall survival; prognostic biomarker; retrospective cohort study; transfusion dependency; treatment response